(untitled) (Al-Academy, 2023)
This study analyzes the features of historical and modern mosques in Jordan compared to that of Amman. The architecture of the Jordanian mosques reflects the images of great ancient empires and kingdoms of Europe and the Middle East. This has happened due to the geographical position of the country. From the studies of historians and archaeologists, comparative analysis of planning solutions, the use of plastics and decor of the facades of mosques, and the literature on the construction methods of the mosques allow us to conclude that age-old traditions have been preserved through the establishment of mosques in both the countries. Besides, the emergence of new features in constructing mosques has been observed. We find the influence of western architecture in the modern-day architectural designs of Jordanian religious establishments. Meanwhile, in the architecture of Amman mosques, a type of small temple is noticed, the volumetric-plastic composition of which is solved in an innovative way, not to resembling historical temples. In constructing mosques, Amman focuses on preserving the identity and spirituality of the mosques but adds new metaphors by ensuring multidimensionality of space and adopting the architectural designs of modern cities. Changes in the architecture of mosques happened due not only to new technologies and materials but, also to integrate with the processes of globalization and international cooperation of architects. We observe the construction of ancient mosques in both the countries combined both European and American architecture which reveals new images and possibilities of the architecture of the East.